Navigating the infodemic minefield: theorizing conversations in the digital sphere - Ashwani Kumar Upadhyay; Komal Khandelwal; Sukrit Dhingra; Geetanjali Panda (Cogent Arts & Humanities)
The study uses a relevant theoretical lens and an exploratory qualitative research approach to examine the dynamics of how an overabundance of information in the digital public sphere combined with fake news during the Covid-19 pandemic led to an infodemic. The study explores the viewpoints of 30 trained fact-checkers through in-depth interviews to learn more about their perspectives on the causes of the infodemic, tools for validating and spotting fake news, the role of the World Health Organization (WHO) in managing the infodemic, and the benefits and drawbacks of employing artificial intelligence (AI) for fact-checking. Additionally, the paper critically examines how the spread of false information contributed to the infodemic that worsened the Covid-19 outbreak. The study uses theories for understanding the core causes and motivating factors behind people’s excessive involvement in spreading false information online. The findings show how the WHO works with the national government and social media platforms to combat false information and provide accurate information. The research contributes to a deeper understanding of how AI, false information, and the global health issues interact by using theoretical perspectives. The work lays the way for efficient methods of controlling the flow of information during a crisis.